Ecotoxicidade da vinhaça para o peixe mato grosso (Hyphessobrycon eques) e para a macrófita lentilha d’água (Lemna minor) - da Silva, Adilson Ferreira [UNESP]; Carraschi, Silvia Patrícia [UNESP]; Gírio, Ana Cristina Fausto [UNESP]; Neto, Antônio Nader [UNESP]; da Cruz, Claudinei; Pitelli, Robinson Antonio [UNESP] (My University, 2015)
The aims of this study were to evaluate the possibility of using the tetra-serpae fish (Hyphessobrycon eques) and macrophyte duckweed (Lemna minor) as biomarkers of toxicity of vinasse, estimating the LC50 and mortality percentages of the test organisms in the period crop of sugarcane. The concentrations tested were: 0.5; 1.0; 1.5; 2.0; 2.5; 3.0; 3.5; 4.0; 4.5; 5.0; 7.5 and 10% vinasse, with three fish per repetition and three repetitions, and the macrophytes were exposed to: 1.0; 3.0; 5.0 and 7.0% of vinasse, with 12 fronds per repetition and three repetitions, both completely randomized design in tests (CRD). The LC50 values for fish ranged from 0.75 to 7.72% and macrophyte, 1.30 to 4.27%. The biomarkers H. eques (fish tetra serpae) and L. minor (macrophyte duckweed) can be used in ecotoxicological effluent vinasse ratings, which is very toxic to fish during the months of August and September and toxic for fish and for macrophyte duckweed in the remaining months of trial.
Ecotoxicity of vinasse for fish tetra-serpae (Hyphessobrycon eques) and macrophyte duckweed (Lemna minor)
Keywords: Ecotoxicology; Sensitivity; Wastewater